Pengaruh Faktor Personality dan Faktor Cognitive Terhadap Niat Penggunaan Teknologi Internet (Studi Empiris Mahasiswa Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Ambarsari, Fina, Dr. Noer Sasongko, SE., M.Si., Ak (2016)
This research compares two factors of intention to use internet. The first factors is personality and second model is cognitive. The subjects of this research are 94 respondents S1 in major Accounting Faculty Economic and Business Muhammadiyah University of Surakarta. This research used survey method with questionnaire instrument and the sample was taken using non probability sampling method, namely convenient sampling. The findings of this research are computer anxiety, affect, trust, perceived usefulness, and perceived ease to use have significant influence on the intention to use internet.